2021
DOI: 10.1371/journal.pone.0255723
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence among pregnant women attending antenatal care services in the rural Gambia

Abstract: Background Intimate partner violence (IPV) refers to any behavior by either a current or ex-intimate partner or would-be rejected lover that causes physical, sexual, or psychological harm. It is the most common form of violence in women’s lives. According to a World Health Organization report, about 1 in 3 women worldwide experience at least one form of IPV from an intimate partner at some point in her life. In the Gambia, about 62% of pregnant women experience at least one form of violence from an intimate pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
2
6
2
Order By: Relevance
“…The prevalence found in this study is similar to those of other studies conducted in Asia–Pacific countries including Bangladesh [ 46 ] and Afghanistan [ 47 ]. However, the finding in this current study is higher than those found in prior studies, which include 39% in India [ 48 ], 40% in Pakistan [ 49 ], and 45.3% in Bangladesh [ 50 ], but lower than 82.7% in rural Bangladesh [ 51 ], and 67% in the Gambia [ 52 ]. The high prevalence of IPV found in this research may be a result of the country's rigid conventional attitudes and gender standards, as well as poor access to public health education, justice, and social services, which have been reported to influence IPV perpetration [ 47 , 53 , 54 ].…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…The prevalence found in this study is similar to those of other studies conducted in Asia–Pacific countries including Bangladesh [ 46 ] and Afghanistan [ 47 ]. However, the finding in this current study is higher than those found in prior studies, which include 39% in India [ 48 ], 40% in Pakistan [ 49 ], and 45.3% in Bangladesh [ 50 ], but lower than 82.7% in rural Bangladesh [ 51 ], and 67% in the Gambia [ 52 ]. The high prevalence of IPV found in this research may be a result of the country's rigid conventional attitudes and gender standards, as well as poor access to public health education, justice, and social services, which have been reported to influence IPV perpetration [ 47 , 53 , 54 ].…”
Section: Discussioncontrasting
confidence: 93%
“…This could be related to cultural beliefs and customs including male dominance in decision-making, female inheritance, polygamy, and religious issues, which could make disclosing any IPV experience in rural PNG difficult [ 65 ]. It is also likely that there was under-reporting among rural women in PNG, which could be related to the sensitivity around gender-based abuse and discussing female issues in the PNG environment, including rejection, embarrassment, or stigma connected with domestic violence [ 52 , 66 ]. As a result, more research is required to explain why there are discrepancies between rural and urban women in PNG.…”
Section: Discussionmentioning
confidence: 99%
“…A health facility-based cross-sectional study conducted in rural Gambia of 373 pregnant women reported the IPV prevalence of 67%. 25 Another cross-sectional study done in a teaching hospital in Gambia of 136 pregnant women reported the IPV prevalence of 61.8%. 26…”
Section: Introductionmentioning
confidence: 99%
“…There are also studies conducted in other African countries mentioning a higher IPV prevalence rate than found in our study. For instance, in Kenya-66.9% ( 36 ) and Gambia-67% ( 10 ). This variation could be due to the fact that women's health is getting global attention and violence against women is nowadays considered to be a violation of human rights.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of IPV ranged from 4–54% worldwide ( 8 ). Other studies conducted in Uganda and Gambia revealed IPV during pregnancy was 40.6 and 67%, respectively ( 9 , 10 ). In Ethiopia, the pooled prevalence of IPV was 26.1% in 2018 ( 11 ).…”
Section: Introductionmentioning
confidence: 87%